2004
DOI: 10.1177/0032885504265485
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Substance Use in Prison: The California Department of Corrections Drug Reduction Strategy Project

Abstract: Inmate welfare, staff security, public health concerns, and the need for recovery-friendly prison environments have been cited as supporting efforts to control in prison substance use. This article reports on the California Department of Corrections (CDC) Drug Reduction Strategy Project, which involved systematic random urine testing and drug interdiction measures. The two-phase evaluation took place at four CDC institutions, with three serving as test sites and one serving as a standard-procedures comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
(3 reference statements)
1
14
0
1
Order By: Relevance
“…Although non-Hispanic white males were more likely to have substance use problems than African American and Hispanic males, this is likely due in part to their greater likelihood of living in the community. Substance use problems are likely less common in prison due to decreased access to substances and random testing for substance use [36]. Although our findings suggest that youth are at less risk for substance abuse while incarcerated, drug use is likely to escalate for these youth after release [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although non-Hispanic white males were more likely to have substance use problems than African American and Hispanic males, this is likely due in part to their greater likelihood of living in the community. Substance use problems are likely less common in prison due to decreased access to substances and random testing for substance use [36]. Although our findings suggest that youth are at less risk for substance abuse while incarcerated, drug use is likely to escalate for these youth after release [37].…”
Section: Discussionmentioning
confidence: 99%
“…Kao primer dobre prakse mogu da posluže SAD, koje ulažu velika finansijska sredstva u najsavremeniju opremu za detekciju droga, obuku zaposlenih, ometanje doturanja, kontrolu urina i jonske skenere (Ilijić i Jovanić, 2015). Intervencije zasnovane na iznenadnim pregledima urina i sankcionisanje za pozitivan test u američkim državama Kalifornija, Pensilvanija i Viskonsin, uticali su kako na smanjenje zloupotrebe droga u zatvorima, tako i na smanjen broj napada na osoblje zatvora i sukobe među osuđenima (Prendergast, Campos, Farabee, Evans & Martinez, 2004). Takođe, trebalo bi razviti i uvesti adekvatne mehanizme procene, koji bi diferencirali osuđene koji ulaze u zatvor sa problemima zavisnosti i psihičkim problemima, kako bi bili podvrgnuti adekvatnom tretmanu u odgovarajućem okruženju.…”
Section: Zaključak I Implikacijeunclassified
“…This research was conducted by Prendergast, Campos, Farabee, Evans, and Martinez (2004) in California and Shewan, Reid, Macpherson, Davies, and Greenwood (2001) in Scotland. Prendergast et al (2004) did not indicate the gender of the sample in their report. Information regarding gender was obtained, however, from the California Department of Corrections and Rehabilitation (2000) .…”
Section: Male-only Samplesmentioning
confidence: 99%
“…They were listed according to the gender make-up of the samples of participants. Four of the studies (Dowden & Blanchette, 2002;Hall et al, 2004;Prendergast et al, 2004;Turley et al, 2004) found favorable impact of the treatment groups on substance usage and=or on recidivism rates. One study found that the control group had more impact than the treatment group (Neale & Saville, 2004).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%